Como as condiç\~oes do mercado de trabalho influenciam as transiç\~oes do desemprego para o emprego? - Maurício Cortez Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This paper analyzes the unemployment duration in Brazil between 2012 and 2017, comparing two very different points in time. There was substantial disparity in labor market conditions over the period investigated. The period 2012-2013 had low unemployment rates, whereas the unemployment rate reached high levels in the period 2016-2017. According to estimates, high levels of unemployment are associated with a lower probability of finding a job. The results also show that reductions in the rates of transition from unemployment to better jobs are more accentuated than those related to low quality jobs during recessions.
Keywords: J23; J64; J22; 330; unemployment duration; business cycle